Executive Functions are Independently Associated with Cognitive Dispersion in HIV Disease - Penheiro, Romeo; Webber, Troy A; Kiselica, Andrew M; Woods, Steven Paul (Archives of clinical neuropsychology, 2025)
People with HIV (PWH) can demonstrate elevated cognitive intraindividual variability (IIV-dispersion) that is associated with everyday functioning problems. Higher IIV-dispersion is theorized to reflect lapses in executive aspects of cognitive control, but few studies have directly evaluated this possibility. 72 PWH completed the Cogstate and clinical measures of executive functions, psychomotor speed, and episodic memory. IIV-dispersion was calculated with the coefficient of variation (CoV) from six age-adjusted Cogstate subtest scores. Multiple regression showed that the three domain-level cognitive predictors explained 8% of the variance in Cogstate CoV (p = .03). Within this model, poorer executive functions were moderately associated with higher Cogstate CoV (p = .01), but the psychomotor and episodic memory domains were not (ps > .05). Findings align with cognitive theory in demonstrating IIV-dispersion is uniquely associated with independent measures of executive functions among PWH. Future experimental and mechanistic studies are needed to determine the precise executive aspects of IIV-dispersion.